2015
DOI: 10.1097/gco.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Community-based provision of family planning in the developing world

Abstract: Decades of previous research on community-based family planning has focused on the traditional community health worker. Yet, recent developments in this field have expanded many areas that have been studied previously. A major emphasis of recent research has dealt with broadening the community-based locations from which clients can obtain injectable contraception. Drug shops in developing countries are promising locations for family planning services. They are ubiquitous, frequently accessed, and generally sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Such implementation strategies may include less frequent PrEP visits and expanding the pool of providers who might be able to screen and provide PrEP beyond the few clinicians and nurses (e.g., training and empowering HIV testing counselors and community health workers or peer educators). These approaches have already been successfully implemented to expand access to injectable and implants contraceptive methods in FP clinics in many African countries using community health workers [2124]. Similar approaches, commonly described as differentiated care services, are currently being promoted for stable virally suppressed HIV-infected persons in many HIV treatment programs in Africa [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Such implementation strategies may include less frequent PrEP visits and expanding the pool of providers who might be able to screen and provide PrEP beyond the few clinicians and nurses (e.g., training and empowering HIV testing counselors and community health workers or peer educators). These approaches have already been successfully implemented to expand access to injectable and implants contraceptive methods in FP clinics in many African countries using community health workers [2124]. Similar approaches, commonly described as differentiated care services, are currently being promoted for stable virally suppressed HIV-infected persons in many HIV treatment programs in Africa [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of lacking access to public health clinics or stock-outs of contraceptives, drug stores can form an important supplier of condoms and pills, thereby increasing the availability of family planning methods (Malkin & Stanback, 2015). Various studies have shown that drugs stores tend to be preferred over public health clinics because of more convenient locations and openings hours (see Malkin & Stanback, 2005 for an overview).…”
Section: Increase the Physical And Social Accessibility Of Contraceptmentioning
confidence: 99%
“…Various studies have shown that drugs stores tend to be preferred over public health clinics because of more convenient locations and openings hours (see Malkin & Stanback, 2005 for an overview). Yet, shop providers need to be well-informed and instructed about the contraceptive methods in order to guarantee the safety of the practise (Malkin & Stanback, 2015).…”
Section: Increase the Physical And Social Accessibility Of Contraceptmentioning
confidence: 99%